THE OVERVIEW OF SURGICAL SITE INFECTION OF PASCA CAESAREAN SECTION AT ARIFIN ACHMAD GENERAL HOSPITAL OF RIAU PROVINCE 1 JANUARY – 31 DECEMBER 2014 PERIOD - Muttaqien, M. Imam; Hamidy, Muhammad Yulis; Rustam, Ruza Prima (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCaesarean section has high risk of surgical site infection (SSI). This research explain about surgical site infection after caesarean section in RSUD Arifin Achmad Province of Riau 1 January – 31 December period. The method of this research is retrospective descriptive. The source of data were taken from medical record of patient that underwent caesarean section in RSUD Arifin Achmad Province of Riau. This research found 573 patients that underwent caesarean section in 2014. The number of SSI in this research is 3.49% (20 patients). Based on the characteristics, the SSI were found most in the age of 18-34 years, the normal nutritional status and obesity level one and level of elementary education. Based on preoperative condition, the SSI were found most in the preoperative hemoglobin ≥11 g/dl, preoperative diagnosis with the complications and were not given prophylactic antibiotics. Based on intraoperative conditions, the SSI were found most in cito surgery, Pfannenstiel incision and amount of bleeding <1000 ml with an average duration of surgery 58.75 minute. Based on postoperative condition, the SSI were found most in the period <5 days. The conclusion from this research is the incidence of surgical site infection after caesarean section at Arifin Achmad 1 January – 31 December period is good enough according to the prevalence of the SSI in Indonesia.Key word : surgical site infection, caesarean section, feature of patient